(untitled) (Między Oryginałem a Przekładem, 2019)
How to Explain a Cat’s Viewpoint? (On Russian Translations of Wisława Szymborska’s Poem Cat in an Empty Apartment) This paper deals with some difficulties related to Russian translations of Wisława Szymborska’s poem Cat in an empty apartment. The question of presence and visibility of lyrical subject in the original text and its translations is one of the major issues presented in the article. An analysis of N. Astafiewa’s and N. Gorbaniewska’s tranlations has been conducted with special respect to the agentivity phenomenon on the level of verb forms. Linguistic categorization has also been mentioned. The author tries to present how differently Russian translators, who perform their typical role of poetry translators, strive for faithfulness of form and content of the original text and in what manner their solutions can influence the lyrical subject’s viewpoint.